Literatury wschodniosłowiańskie na łamach pisma „Warmia i Mazury” w latach 1980-1990 - Rudziewicz, Irena (Acta Polono-Ruthenica, 2004)
The paper analyses the articles published in the Polish periodical „Warmia and Mazury” in the years 1980-1990 and devoted to the East Slavic culture and literature, particularly the works of A. Achmatova, A. Blok, J. Brodsky, V. Vysocky, M. Lermontov, A. Pushkin, M. Cvetayeva, M. Gorky and A. Czekhov.